Young people's everyday securities: pre-emptive and pro-active strategies towards ontological security in Scotland. (4th May 2019) - Botterill, Kate; Hopkins, Peter; Sanghera, Gurchathen Singh
Abstract: This paper uses a framework of 'ontological security' to discuss the psychosocial strategies of self-securitisation employed by ethnic and religious minority young people in Scotland. We argue that broad discourses of securitisation are present in the everyday risks and threats that young people encounter. In response and as resistance young people employ pre-emptive and pro-active strategies to preserve ontological security. Yet, these strategies are fraught with ambivalence and contradiction as young people withdraw from social worlds or revert to essentialist positions when negotiating complex fears and anxieties. Drawing on feminist geographies of security the paper presents a multi-scalar empirical analysis of young people's everyday securities, connecting debates on youth and intimacy-geopolitics with the social and cultural geographies of young people, specifically work that focuses upon young people's negotiations of racialised, gendered and religious landscapes.